2011
DOI: 10.3904/kjim.2011.26.3.304
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor E2-related factor 2 Dependent Overexpression of Sulfiredoxin and Peroxiredoxin III in Human Lung Cancer

Abstract: Background/AimsOxidative stress results in protein oxidation and is implicated in carcinogenesis. Sulfiredoxin (Srx) is responsible for the enzymatic reversal of inactivated peroxiredoxin (Prx). Nuclear factor E2-related factor 2 (Nrf2) binds to antioxidant responsive elements and upregulates the expression of Srx and Prx during oxidative stress. We aimed to elucidate the biological functions and potential roles of Srx in lung cancer.MethodsTo study the roles of Srx and Prx III in lung cancer, we compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…The initial correlation of Srx to cancer emerged from its differential expression in the transformation-sensitive mouse JB6 epidermal cells [36]. It was further demonstrated that Srx is overexpressed in cancers of skin, lung, and rectum, but not in normal tissues, and has an oncogenic role in promoter-induced tumorigenesis of skin and colon, and in lung cancer cells [24][25][26]37,38], indicating that Srx might be targeted for cancer prevention or treatment. Here, we showed that the inhibition of Srx activity in human lung adenocarcinoma A549 cells causes oxidative stress, which in turn leads to mitochondrial damage resulting in apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial correlation of Srx to cancer emerged from its differential expression in the transformation-sensitive mouse JB6 epidermal cells [36]. It was further demonstrated that Srx is overexpressed in cancers of skin, lung, and rectum, but not in normal tissues, and has an oncogenic role in promoter-induced tumorigenesis of skin and colon, and in lung cancer cells [24][25][26]37,38], indicating that Srx might be targeted for cancer prevention or treatment. Here, we showed that the inhibition of Srx activity in human lung adenocarcinoma A549 cells causes oxidative stress, which in turn leads to mitochondrial damage resulting in apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have shown that Srx is induced by a variety of stimuli or chemicals that result in oxidative damage in Srx-deficient cells [21,22]. It was reported that an enhanced level of Srx promotes cell proliferation [23], and Srx is highly expressed in several human tumors including skin tumors, rectal carcinoma and lung adenocarcinoma, compared with the levels found in corresponding normal tissues [24,25]. Srx was also found to be required for anchorage-independent colony formation by human lung cancer cells and for cell migration and invasion in vitro, as well as for the formation of metastases by these cells in vivo [26].…”
Section: Introductionmentioning
confidence: 98%
“…Knockdown of Srx also impaired c-Jun phosphorylation and markedly attenuated AP-1-dependent luciferase reporter activity, suggesting that Srx functions as a positive regulator of c-Jun activation in addition to being a target of AP-1 activation. Screening of human tissue by microarray analysis revealed the level of Srx expression to be increased in tumors, including those of the skin, lung, and rectum, compared with that in corresponding normal tissue [41,49]. Srx was also found to be required for anchorage-independent colony formation by human lung cancer cells and for cell migration and invasion in vitro, as well as for the formation of metastases by these cells in vivo [50].…”
Section: Transcriptional Regulation Of Srx Expression Via Activator Pmentioning
confidence: 96%
“…It may also enhance cell migration in lung cancer in a Prx-independent manner by interacting with S100A4 ( a calcium binding protein ) and non-muscle myosin IIA (NMIIA) [49]. Aberrant expression of Srx in lung squamous cell carcinoma, lung adenocarcinoma, and pancreatic cancer is correlated with poor survival in those patients [71; 72; 73]. Srx protein is also over-expressed in renal cell carcinoma where it is proposed to be a good antibody target that can result in tumor cell death [74].…”
Section: The Srx-prx Axis In Tumorigenesis and Cancer Progressionmentioning
confidence: 99%